Simultaneous construction strategy using two types of fluorescent markers for HVT vector vaccine against infectious bursal disease and H9N2 avian influenza virus by NHEJ-CRISPR/Cas9 - Zhang, Jun-Feng; Shang, Ke; Kim, Sang-Won; Park, Jong-Yeol; Wei, Bai; Jang, Hyung-Kwan; Kang, Min; Cha, Se-Yeoun (Frontiers in Veterinary Science, 2024)
Recently, herpesvirus of turkeys (HVT), which was initially employed as a vaccine against Marek's disease (MD), has been shown to be a highly effective viral vector for producing recombinant vaccines that can simultaneously express the protective antigens of multiple poultry diseases. Prior to the development of commercial HVT-vectored dual-insert vaccines, the majority of HVT-vectored vaccines in use only contained a single foreign gene and were often generated using time-consuming and inefficient traditional recombination methods. The development of multivalent HVT-vectored vaccines that induce simultaneous protection against several avian diseases is of great value. In particular, efficacy interference between individual recombinant HVT vaccines can be avoided. Herein, we demonstrated the use of CRISPR/Cas9 gene editing technology for the insertion of an IBDV (G2d) VP2 expression cassette into the UL45/46 region of the recombinant rHVT-HA viral genome to generate the dual insert rHVT-VP2-HA recombinant vaccine. The efficacy of this recombinant virus was also evaluated in specific pathogen-free (SPF) chickens. PCR and sequencing results showed that the recombinant virus rHVT-VP2-HA was successfully constructed. Vaccination with rHVT-VP2-HA produced high levels of specific antibodies against IBDV (G2d) and H9N2/Y280. rHVT-VP2-HA can provide 100% protection against challenges with IBDV (G2d) and H9N2/Y280. These results demonstrate that rHVT-VP2-HA is a safe and highly efficacious vaccine for the simultaneous control of IBDV (G2d) and H9N2/Y280.